SIGNIFICANCE OF SEMICONDUCTORS IN MODERN USE - Adilova Xalida Shamshetdin qızı; Akimbaev Ruslan Farxodovich; O'rinbayev Sharofiddin Maksudbay o'g'li (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: This article deals with the importance of semiconductors and its in the modern world